2017
DOI: 10.3906/vet-1704-39
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida strains with nested PCR in bovinemastitis and determination of antifungal susceptibilities

Abstract: Mastitis is one of the biggest problems of dairy cattle industries. In recent years, fungal agents have been frequently reported among the causative agents for mastitis. Among the fungal agents, Candida species are the most common. This study's aims were the isolation, identification, and determination of antifungal susceptibility of Candida species causing mycotic mastitis in cattle. A total of 260 mastitic milk samples were collected from different farms. Identification was conducted by rapid diagnostic test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
6
12
0
2
Order By: Relevance
“…In this study, Candida species of yeasts were isolated in the 23.44% (60/256) of all samples analyzed. This rate is a marginally higher than the rates reported in Turkey were 12.7% [ 9 ], 17.7% [ 10 ]; the rates reported in Brazil were 17.3% [ 4 ], 12.8% [ 11 ]; and the rate reported in Slovenia was 7.5% [ 12 ]. C. krusei was the predominant species isolated in this study, which was 23.33% (14/60) of the Candida isolates from those with clinical mastitis.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this study, Candida species of yeasts were isolated in the 23.44% (60/256) of all samples analyzed. This rate is a marginally higher than the rates reported in Turkey were 12.7% [ 9 ], 17.7% [ 10 ]; the rates reported in Brazil were 17.3% [ 4 ], 12.8% [ 11 ]; and the rate reported in Slovenia was 7.5% [ 12 ]. C. krusei was the predominant species isolated in this study, which was 23.33% (14/60) of the Candida isolates from those with clinical mastitis.…”
Section: Discussionmentioning
confidence: 72%
“…However, the rate of C. krusei isolates of our finding was higher than others. Ruz-Peres et al reported a 18.18% [ 13 ], ErbaŞ et al reported a 17.4% [ 10 ], Ksouri et al reported a 15.57% [ 14 ], Krukowski et al reported a 15.5% [ 15 ], and Eldesouky et al reported a 12.2% of C. krusei isolates in cow mastitis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian tersebut juga membuktikan bahwa metode PCR secara signifikan mampu membedakan C. albicans lebih akurat dan cepat dibandingkan dengan metode konvensional. Erbaş et al (2017) telah berhasil mengidentifikasi Candida sp. dengan metode identifikasi cepat menggunakan API 20 C AUX dan nested PCR dari sampel susu penderita mastitis.…”
Section: Diagnosa Mastitis Mikotikunclassified
“…Prevalensi mastitis mikotik biasanya sangat rendah dibandingkan dengan agen penyebab mastitis lainnya tetapi secara signifikan meningkat selama dekade terakhir (Erbaş et al, 2017). Salah satu penyebab meningkatnya insiden mastitis mikotik diduga adalah penggunaan antibiotik jangka panjang yang tidak terkontrol dan penggunaan preparat steroid dalam terapi tanpa didahului identifikasi penyebabnya (Rayaz and Darand, 2013).…”
unclassified